Analysis of demand in the importation process for the trade of individual protection equipment - Toledo, Tatiane Chiles (2017)
The organizations maintain excessive inventories as a way to anticipate the customer's need, taking, this way, competitive advantage. On the other hand, the lack of stocks can stop assembly lines; change the production schedule; increase costs and harm the marketing planning. However, there are costs in relation to these inventories;therefore, set an appropriate policy stock management is a critical factor for the success of a company, in addition to obtaining sustainable competitive advantage in the long term. Considered by many as the basis for managing the supply chain, inventory management depends on clear definitions for the following questions: how much to ask, when to ask, how much to keep in stock and where to find the stock. Therefore, there must be a balance in relation to demand and stock supply. Increased market competitiveness forces companies to lower their stock costs and may result in loss of orders due to lack of product. This paper describes the process of forecasting demand, and the methods of analysis forecasting as a tool to reduce costs by simulating the methods of demand forecasting in order to improve the level of stock. Thus, a case study was elaborated in the ABC Company, which acts in the imported PPE business for analyzing the process and simulating the techniques of demand forecasting.The results presented in the case study were satisfactory actually observed divergence between the process applied before the company and applied studies directly on demand obtained with this assertiveness in the forecast.